A Panpsychist Dead End. (2nd July 2021) - Nagasawa, Yujin
Abstract: Panpsychism has received much attention in the philosophy of mind in recent years. So-called constitutive Russellian panpsychism, in particular, is considered by many the most promising panpsychist approach to the hard problem of consciousness. In this paper, however, I develop a new challenge to this approach. I argue that the three elements of constitutive Russellian panpsychism—that is, the constitutive element, the Russellian element and the panpsychist element—jointly entail a 'cognitive dead end'. That is, even if constitutive Russellian panpsychism is true, we cannot ascertain how it might solve the hard problem of consciousness.